A microcalorimeter for simultaneous measurement of the electric and thermal transport coefficients in ferromagnetic thin films. (2nd July 2018) - Srichandan, S; Kronseder, M; Vogel, M; Back, C H; Strunk, C
Abstract: A SiN x based suspended platform has been developed that allows for the simultaneous measurement of the transport coefficients, namely the resistivity ρ, thermopower, and thermal conductivity κ . We describe the calorimeter fabrication and the characterization of the set-up required to enable quantitative experiments. The temperature distribution of a typical device is numerically simulated to verify the spatial homogeneity. The method is illustrated for Pd x Ni1− x and Co x Fe1− x ferromagnetic thin films. We employ a novel double bridge technique that allows for an accurate determination of the thermal conductivity.